Salah al-Dïn al-Ayyubi and the Crusaders - Khoury, Loulou AL-AkL (International Journal of Social Sciences: Current and Future Research Trends, 2022)
Salah al-Dïn lived in a spiritual and strategic environment which he took forward. At al-Adïb and Nur al-Dïn’s death, he rose to power. Yet, diplomatic arrangements to keep truce with the Franks could not be sustained indefinitely. The occasion to wage war presented itself which led to the victory of Hattin. His main objective was Jerusalem. As the Hattin campaign absorbed the majority of the Frankish troops and there was no prospect of relief, time to surrender Jerusalem arrived. Jerusalem back in Muslim hands, the holy sites needed restoration. To consolidate his hold on the Near East, Salah al-Dïn had to conquer the remaining Frankish lands. Priority was the port of Tyre, but this could not be achieved. Exhaustion due to years of war, continuous diplomatic encounters and tests of strengths and weaknesses exhausted Salah al-Dïn who died age 56. Yet, questions are still to be viewed holistically and cross-culturally.